Panel material of thermal insulation board and preparation method of panel material

By optimizing the formulation and molding process of the panel materials, the problems of low strength and poor corrosion resistance of the thermal insulation board panel materials have been solved, and a cement-based panel with high strength, crack resistance and durability has been achieved, which is suitable for thermal insulation of building exterior walls.

CN120774667APending Publication Date: 2025-10-14娄底潇湘职业学院
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410412034.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

The panel materials of existing thermal insulation panels have low strength, are easy to break, and have poor corrosion resistance, resulting in a short service life and safety hazards, especially when they are easily fallen off during installation on building exterior walls.

Method used

The panel slurry formula with a specific ratio, including cement, quartz sand, fly ash, silica fume, graphene oxide grafted carbon fiber, etc., is vacuum pressed and combined with low-heat cement and reasonably graded quartz sand to improve the compressive strength, flexural strength and corrosion resistance of the panel and reduce drilling cracks.

Benefits of technology

Achieve high compressive strength, flexural strength and corrosion resistance at thin thickness, extend service life, reduce maintenance costs, improve safety, and reduce the risk of cracks caused by temperature changes and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a panel material of a thermal insulation board, which is formed by curing panel slurry. The panel slurry is prepared from 26%-34% of cement, 38%-50% of quartz sand, 3%-10% of secondary coal ash, 2%-4% of silica fume, 0.6%-3% of a water reducing agent, 0.1%-1% of a defoaming agent, 0.1%-2% of an alkaline exciting agent, 0.1%-0.8% of graphene oxide grafted carbon fibers, 0.05%-1.5% of carboxymethylcellulose, 0.05%-1% of sodium gluconate, 0.8%-2.5% of an anti-corrosion inhibitor, 0.5%-2% of low-temperature water-based emulsion and 10%-16% of water. The sum of the percentages of the components is 100%. The panel prepared by the invention has the advantages of high compressive strength, breaking strength and corrosion resistance under the condition of smaller thickness (0.3-2cm), difficulty in cracking during drilling and the like, the service life of the thermal insulation board is prolonged, and the safety of the thermal insulation board is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a panel material for a thermal insulation board and a preparation method thereof. Background Art

[0002] The construction industry achieves thermal insulation by installing thermal insulation panels on the surface of building walls, effectively reducing energy consumption and carbon emissions during the building's operation phase. Insulation panels are often composed of a double-layer laminate or sandwich structure, consisting of a relatively rigid outer panel and a core material with low thermal conductivity. However, the panels must meet certain requirements, such as high strength (high compressive and flexural strength) and resistance to cracking to withstand certain loads such as transportation, stacking, drilling, gluing, and fixed installation. They also need to be corrosion-resistant to withstand erosion from wind, sun, and acid rain. Furthermore, the panel thickness must be limited, otherwise the insulation panel will be too heavy, making it more likely to fall off after installation on the exterior wall. While increasing the panel thickness does enhance its strength and reduce the chance of cracking during drilling and installation, excessive panel thickness also increases the overall thickness of the insulation panel, which can increase the difficulty and stability of installation on the building's exterior wall.

[0003] However, some thermal insulation panels currently on the market still have defects such as "low strength, easy breakage, poor corrosion resistance and short lifespan", which greatly increases the frequency and cost of later maintenance of the insulation panels. Especially for thermal insulation panels installed on the exterior walls of buildings, they are very easy to fall off and cause falling objects from high altitudes. At the same time, later maintenance requires high-altitude operations, which poses a huge safety hazard. Summary of the Invention

[0004] (1) Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a panel material for a thermal insulation board and a preparation method thereof. The panel has the advantages of high compressive strength, flexural strength, corrosion resistance and not prone to cracks when drilled at a relatively thin thickness (0.3-2 cm). It solves the technical problems of low strength, low corrosion resistance, easy cracks when drilled or large panel thickness of the existing thermal insulation board panel material, thereby improving the service life and safety of the thermal insulation board.

[0006] (2) Technical solution

[0007] The present invention provides a panel material for a thermal insulation board, which is formed by curing panel slurry. The panel slurry has the following formula, calculated by mass percentage: 26-34% of cement, 38-50% of quartz sand, 3-10% of secondary fly ash, 2-4% of silica fume, 0.6-3% of water reducer, 0.1-1% of defoamer, 0.1-2% of alkaline activator, 0.1-0.8% of graphene oxide grafted carbon fiber (CF-GO), 0.05-1.5% of carboxymethyl cellulose, 0.05-1% of sodium gluconate, 0.8-2.5% of anti-corrosion inhibitor, 0.5-2% of low-temperature aqueous emulsion, and 10-16% of water; the sum of the percentages of the aforementioned components is 100%.

[0008] According to a preferred embodiment of the present invention, the water-cement ratio of the panel slurry is 0.4-0.45, preferably 0.43. The water-cement ratio is the mass ratio of water to cement.

[0009] According to a preferred embodiment of the present invention, the mortar-sand ratio of the panel slurry is 0.87-0.92, preferably 0.9. The mortar-sand ratio is the mass ratio of the gel material (cement + fly ash + silica fume) to the sand.

[0010] According to a preferred embodiment of the present invention, the cement is a mixture of one or more of grades 42.5, 42.5R, 52.5, 52.5R, 62.5, and 62.5R, and is preferably low-heat cement or medium-heat cement.

[0011] Low-heat cement and medium-heat cement have lower hydration heats than ordinary Portland cement. Hydration heat refers to the amount of heat released during the hydration reaction between cement and water. Ordinary Portland cement has hydration heats of 50-80 kcal / g of cement after 7 and 28 days, respectively. Cement with a hydration heat lower than that of ordinary Portland cement is designated as low-heat or medium-heat cement.

[0012] According to a preferred embodiment of the present invention, the quartz sand has a particle size of less than 5mm, and is preferably composed of quartz sands with particle sizes of 0.1-1mm, 1-3mm, and 3-5mm in a weight ratio of 2-4:5:1-3, preferably 3:5:2. The selected quartz sand particle size reduces the void ratio between aggregates, increases interfacial adhesion, and improves the mechanical strength, corrosion resistance, and drilling crack resistance of the panel.

[0013] According to a preferred embodiment of the present invention, the silica fume has a particle size of 0.1-0.2 μm and a silicon content greater than 90%. Mineral admixtures such as fly ash and silica fume can improve the microstructure of the cement paste, increase early strength, shorten curing and demolding time, and enhance the panel material's later crack resistance.

[0014] According to a preferred embodiment of the present invention, the water reducer is a high-performance polycarboxylic acid water reducer (a pale yellow liquid) with a water reduction rate of 25-30%. This water reducer also serves as a fiber dispersant. The water reducer reduces the amount of water added, lowering the water-cement ratio (0.4-0.45), improving the panel material's performance while reducing shrinkage caused by water evaporation.

[0015] According to a preferred embodiment of the present invention, the defoamer is a polyether defoamer (a colorless, transparent liquid) with a solids content of 40-50%. The defoamer can reduce the number of pores in the product, making the panel material surface smoother and more compact after polishing. This not only facilitates the printing of pattern layers or the composite decorative film layer, but also improves the panel material's resistance to environmental and weathering erosion, and enhances its flexural and compressive strengths.

[0016] According to a preferred embodiment of the present invention, the alkaline activator is prepared by mixing a 10-15% sodium hydroxide solution and water glass in a mass ratio of 1:2. This alkaline activator ensures both effective activation and control of the reaction rate and final product properties. Excessively high sodium hydroxide solution concentrations may result in an overly vigorous reaction and excessive heat release, while too low a concentration may not achieve the desired activation effect.

[0017] According to a preferred embodiment of the present invention, the anti-corrosion inhibitor is preferably SBT-RMA(II) high-efficiency concrete preservative produced by Jiangsu Subote New Materials Co., Ltd. The graphene oxide-grafted carbon fibers (CF-GO) have a diameter of 5-20 μm and a length of 6-10 mm; shorter fibers allow for better dispersion and uniform distribution, thereby effectively improving the panel material's crack resistance and overall mechanical properties.

[0018] According to a preferred embodiment of the present invention, the low-temperature aqueous emulsion is an aqueous polyurethane emulsion or an aqueous polyacrylic acid emulsion or a combination thereof, and has a solid content of 40-45%. The low-temperature aqueous emulsion gives the panel material better deformation ability when subjected to impact or drilling stress, and resists deformation factors such as thermal expansion and contraction, reducing cracks or fissures caused by ambient temperature. The low-temperature aqueous emulsion is combined with graphene oxide grafted carbon fiber (CF-GO) to enable the panel material to have both rigidity enhancement and flexibility toughening, which can significantly improve the crack resistance of the panel material, can be dispersed in cement slurry to absorb and disperse stress, reduce the occurrence and development of cracks, and avoid cracks in the panel material during drilling or installation.

[0019] According to the preferred embodiment of the present application, the preferred formula of the panel slurry is: cement 30%, quartz sand 43%, secondary fly ash 6.9%, silica fume 2.25%, water reducing agent 1%, defoaming agent 0.2%, alkaline activator 0.5%, graphene oxide grafted carbon fiber 0.4%, carboxymethyl cellulose 0.1%, sodium gluconate 0.05%, corrosion inhibitor 1.5%, low-temperature water-based emulsion 1.5%, and water 12.6%.

[0020] In a second aspect, the present application also relates to a method for preparing the panel material of the thermal insulation board, which comprises:

[0021] S1, stirring and mixing the water reducing agent, graphene oxide grafted carbon fiber, low-temperature water-based emulsion, and 30-35% of water to obtain a mixture A;

[0022] S2, dry mixing the cement, quartz sand, secondary fly ash, and silica fume to obtain a mixture B;

[0023] S3, stirring and mixing the mixture A, the mixture B, the defoaming agent, the alkaline activator, the carboxymethyl cellulose, the sodium gluconate, the corrosion inhibitor, and the remaining water to obtain a panel slurry;

[0024] S4, pouring the panel slurry into a mold, laying flat in the mold under vacuum, and pressing and forming under high-frequency vibration, demolding after curing, and polishing to obtain the panel material of the thermal insulation board.

[0025] The panel material of the thermal insulation board is double-layered with the thermal insulation core material or combined into a sandwich structure with the core material in the middle to obtain the thermal insulation board material. The thickness of the panel material is 0.3-2 cm, preferably 0.4-0.7 cm.

[0026] According to the preferred embodiment of the present application, in S4, the pressing and forming pressure is 1.5-3 MPa, and the curing condition is 35-45°C constant temperature water or water vapor environment for 24-48 h.

[0027] The vacuum environment can remove bubbles in the panel material, which helps to improve the strength of the panel material, reduce pores or bubbles, make the polished panel more flat and delicate, improve the corrosion resistance of the panel material, and facilitate printing patterns or composite decorative film layers. Through pressing and forming, pre-stress is applied to the cement sheet, which can offset the tensile stress generated during drilling to some extent and prevent crack formation.

[0028] The combination of the above strategies effectively improves the resistance of the cement thin panel material (0.3-2 cm) to drilling operations.

[0029] In a third aspect, the present invention provides a heat insulation board, which comprises a panel material prepared according to any of the above embodiments, wherein the thickness of the panel material is 0.3-2 cm, and the panel material and the core board material are stacked in a double layer or form a sandwich structure.

[0030] (3) Beneficial effects

[0031] The cement-based panel material of the present invention has high mechanical strength in a very thin state. Its main principles are: 1. Low-temperature aqueous emulsion enables the cement board to have better deformation ability when subjected to impact or drilling stress, thereby improving the thermal expansion and contraction performance of the panel material; 2. Graphene oxide grafted carbon fiber is used for reinforcement. Graphene oxide grafted carbon fiber (CF-GO) has extremely high hydrophilicity and reactivity, which enables CF-GO to be more evenly distributed in the panel slurry system to form a fiber network. This fiber network is like the "reinforcement rib" in the slurry system, which can effectively bear the load and transfer stress, thereby improving the compressive and flexural strength of the panel; the surface of graphene oxide grafted carbon fiber (CF-GO) contains a large number of oxygen-containing active functional groups, which are added to the slurry system to disperse and form a network structure, and serve as the nucleation center of hydration products, providing growth points for hydration products, attracting the deposition and aggregation of hydration products, promoting the formation of hydration products such as calcium silicate gel (CSH) and ettringite crystals, improving the microstructure of the panel, and improving the mechanical strength of the panel material. ③ Low-heat cement or medium-heat cement has a lower heat of hydration, which helps to reduce cracks caused by temperature shrinkage. Quartz sand uses reasonably graded aggregates to reduce the void ratio between aggregates and increase interfacial adhesion. Mineral admixtures such as activated fly ash and silica fume can improve the microstructure of the cement slurry, improve early strength and later crack resistance. The use of water-reducing agent and a low water-cement ratio ensures sufficient workability while reducing shrinkage caused by water evaporation. During the preparation process, the panel is formed under vacuum and pressing force to reduce pores or bubbles, offset the tensile stress generated during the drilling process to a certain extent, and prevent crack formation. In summary, the cement-based panel material of the present invention has high flexural strength, flexural strength, is not prone to cracks, and is resistant to drilling cracking at a relatively thin thickness (0.3-2cm).

[0032] The cement-based panel material of the present application has high corrosion resistance, the main principle of which is that: ① the corrosion inhibitor is mixed in the cement + fly ash / silica fume composite system, so that a larger cluster structure is formed among the corrosion inhibitor, water molecules and eroded sulfate ions, the migration rate of water and sulfate ions to the inside of the cement panel is reduced, the corrosion resistance of the panel material to sulfate and other salts is improved, and the service life of the panel is improved. ② Low heat cement or medium heat cement has lower hydration heat, which helps to reduce cracks caused by temperature shrinkage. The quartz sand uses a reasonable gradation aggregate to reduce the void ratio between the aggregates, so that the panel material is smooth, dense and delicate. The active fly ash, silica fume and other mineral admixtures can improve the microstructure of the cement paste, improve the early strength and later crack resistance; the panel is formed under vacuum and pressure, reducing air holes or bubbles. Through the combination of the above strategies, the speed of the product in the later stage of the environment water vapor or acidic gas eroding through the crack, pore, bubble / air hole to the inside is reduced. Therefore, the cement-based panel material prepared by the present application can effectively resist the corrosion of sulfate and salt substances, reduce the risk of surface expansion, peeling and other risks of the cement panel under the erosion of sulfate and salt substances, and improve the durability of the cement panel. DETAILED DESCRIPTION

[0033] In order to better explain the present application, the present application is described in detail below in combination with specific embodiments.

[0034] Example 1

[0035] The present embodiment provides a preparation method of a panel material of a thermal insulation board, which comprises:

[0036] (1) Preparation of raw materials

[0037] The composition of the panel slurry is: P42.5 cement 30%, quartz sand 43%, secondary fly ash 6.9%, silica fume 2.25%, water reducing agent 1%, defoaming agent 0.2%, alkaline activator 0.5%, graphene oxide grafted carbon fiber 0.4%, carboxymethyl cellulose 0.1%, sodium gluconate 0.05%, corrosion inhibitor 1.5%, low-temperature water-based emulsion 1.5%, and water 12.6%. The water-cement ratio is 0.42; the mortar-sand ratio is 0.91.

[0038] The specifications of each raw material are as follows:

[0039] Cement: low-heat cement of P42.5.

[0040] Quartz sand: the quartz sand with particle sizes of 0.1-1mm, 1-3mm and 3-5mm is mixed in a mass ratio of 3:5:2.

[0041] Silica fume: the particle size of the silica fume is 0.1-0.2μm, and the silicon content is >90%.

[0042] Water reducing agent: polycarboxylic acid high-performance water reducing agent (light yellow liquid), water reducing rate is 28%.

[0043] Defoaming agent: polyether defoaming agent (colorless transparent liquid), solid content is 40%.

[0044] Alkaline activator: 12% concentration of sodium hydroxide solution and water glass are mixed and stirred in a mass ratio of 1:2.

[0045] Graphene oxide grafted carbon fiber: diameter 5-10μm, length 6-10mm.

[0046] Corrosion inhibitor: SBT-RMA(II) concrete corrosion inhibitor produced by Jiangsu Subote New Material Co., Ltd.

[0047] Low temperature water-based emulsion: polyurethane low temperature water-based emulsion, solid content is 45%.

[0048] (2) Preparation process is as follows:

[0049] ①The water reducing agent, graphene oxide grafted carbon fiber, low temperature water-based emulsion, 35% water are stirred and mixed to obtain mixture A.

[0050] ②The cement, quartz sand, secondary fly ash, silica fume are dry mixed to obtain mixture B.

[0051] ③The mixture A, mixture B, defoaming agent, alkaline activator, carboxymethyl cellulose, sodium gluconate, corrosion inhibitor, remaining water are stirred and mixed to obtain panel slurry.

[0052] ④The panel slurry is poured into a mold with a depth of 0.4cm, and is laid flat in the mold under vacuum state and high frequency vibration, and is pressed into shape under the pressure of 1.5MPa, and is demolded after 24h constant temperature water curing at 45℃, and is polished to obtain the panel material of the heat preservation and insulation board.

[0053] Among them, the vibration frequency can be 4000-5000rpm, and the linear vibration speed can be 40-50mm / s. The vibration frequency is mainly used to fully discharge the bubbles in the slurry, so that the slurry is more dense, and the strength and corrosion resistance are improved.

[0054] Example 2

[0055] This example adjusts the slurry formula for the panel material based on Example 1. The adjusted slurry composition is: 34% P42.5 cement, 43.85% quartz sand, 3.0% secondary fly ash, 2.0% silica fume, 0.8% water reducer, 0.1% defoamer, 0.2% alkaline activator, 0.3% graphene oxide grafted carbon fiber, 0.1% carboxymethyl cellulose, 0.05% sodium gluconate, 1.0% corrosion inhibitor, 1.0% low-temperature aqueous emulsion, and 13.6% water. The water-cement ratio is 0.4, and the mortar-sand ratio is 0.89. The raw material specifications and preparation process are similar to those in Example 1.

[0056] Example 3

[0057] This example adjusts the slurry formulation of the panel material based on Example 1. The adjusted slurry composition is: 26% P42.5 cement, 42.5% quartz sand, 7.0% secondary fly ash, 4.0% silica fume, 1% water reducer, 0.6% defoamer, 1.2% alkaline activator, 0.8% graphene oxide grafted carbon fiber, 1.5% carboxymethyl cellulose, 0.5% sodium gluconate, 2.0% corrosion inhibitor, 1.5% low-temperature aqueous emulsion, and 11.4% water. The water-cement ratio is 0.438, and the mortar-sand ratio is 0.87. The raw material specifications and preparation process are similar to those in Example 1.

[0058] Example 4

[0059] The formula of this embodiment is the same as that of embodiment 1, and only the specifications of the raw materials are adjusted as follows:

[0060] Cement: P52.5R low heat cement.

[0061] Quartz sand: Mix quartz sand with particle sizes of 0.1-1mm, 1-3mm, and 3-5mm in a mass ratio of 4:5:1.

[0062] Silica fume: The particle size of silica fume is 0.1-0.2μm, and the silicon content is greater than 90%.

[0063] Water reducing agent: polycarboxylic acid high performance water reducing agent (light yellow liquid), water reducing rate is 28%.

[0064] Defoaming agent: polyether defoaming agent (colorless transparent liquid), solid content is 40%.

[0065] Alkaline activator: Mix 12% sodium hydroxide solution and water glass in a mass ratio of 1:2 and stir until evenly mixed.

[0066] Graphene oxide grafted carbon fiber: diameter 5-10μm, length 6-10mm.

[0067] Anti-corrosion inhibitor: SBT-RMA (Ⅱ) high-efficiency concrete anti-corrosion agent produced by Jiangsu Subote New Materials Co., Ltd.

[0068] Low temperature aqueous emulsion: aqueous polyacrylic acid emulsion with a solid content of 48%.

[0069] Example 5

[0070] The formula of this embodiment is the same as that of embodiment 1, and only the specifications of the raw materials are adjusted as follows:

[0071] Cement: P42.5R medium temperature cement.

[0072] Quartz sand: Mix quartz sand with particle sizes of 0.1-1mm, 1-3mm, and 3-5mm in a mass ratio of 2:5:3.

[0073] Silica fume: The particle size of silica fume is 0.1-0.2μm, and the silicon content is greater than 90%.

[0074] Water reducing agent: polycarboxylic acid high performance water reducing agent (light yellow liquid), water reducing rate is 28%.

[0075] Defoaming agent: polyether defoaming agent (colorless transparent liquid), solid content is 40%.

[0076] Alkaline activator: Mix 12% sodium hydroxide solution and water glass in a mass ratio of 1:2 and stir until evenly mixed.

[0077] Graphene oxide grafted carbon fiber: diameter 5-10μm, length 6-10mm.

[0078] Anti-corrosion inhibitor: SBT-RMA (Ⅱ) high-efficiency concrete anti-corrosion agent produced by Jiangsu Subote New Materials Co., Ltd.

[0079] Low temperature water-based emulsion: polyurethane low temperature water-based emulsion with a solid content of 45%.

[0080] Example 6

[0081] The formula and raw material specifications of this embodiment are the same as those of Example 1, and only the process is adjusted as follows:

[0082] ① A water reducer, graphene oxide grafted carbon fiber, a low-temperature aqueous emulsion, and 30% water were stirred and mixed to obtain a mixture A.

[0083] ② Dry mix cement, quartz sand, secondary fly ash and silica fume to obtain mixture B.

[0084] ③ Mix mixture A, mixture B, defoamer, alkaline activator, carboxymethyl cellulose, sodium gluconate, corrosion inhibitor, and remaining water, and stir to obtain panel slurry.

[0085] ④ Pour the panel slurry into a mold with a depth of 0.4 cm, flatten it in the mold with high-frequency vibration under vacuum, press it into shape under a pressure of 2 MPa, and after curing in a steam room at 45°C for 24 hours, demould it, grind it and polish it to obtain the panel material of the thermal insulation board.

[0086] Comparative Example 1

[0087] This comparative example deletes the graphene oxide grafted carbon fiber used in the panel slurry formula of Example 1, and increases the proportion of the low-temperature aqueous emulsion accordingly.

[0088] Comparative Example 2

[0089] In this comparative example, the low-temperature aqueous emulsion used in the panel slurry formula of Example 1 is deleted, and the proportion of quartz sand is increased accordingly.

[0090] Comparative Example 3

[0091] In this comparative example, the anti-corrosion inhibitor used in the panel slurry formulation of Example 1 was deleted, and the proportion of cement was increased accordingly.

[0092] Comparative Example 4

[0093] In this comparative example, the panel slurry composition was adjusted to: 30% P42.5 cement, 44.55% quartz sand, 4.0% secondary fly ash, 2.0% silica fume, 0.6% water reducer, 0.2% defoamer, 0.5% alkaline activator, 0.4% graphene oxide grafted carbon fiber, 0.1% carboxymethyl cellulose, 0.05% sodium gluconate, 1.1% anti-corrosion inhibitor, 1.5% low-temperature aqueous emulsion, and 15% water. The water-cement ratio was 0.5, and the mortar-sand ratio was 0.81.

[0094] The cement-based panel materials prepared in each of the above examples were tested for compressive strength, flexural strength, and sulfate resistance 3 days after constant temperature water curing. The results are shown in Table 1. The drilling cracking resistance test was performed using a small handheld electric drill with an 8 mm diameter triangular drill bit (masonry bit) and a spacing of 3 cm. Three holes were drilled in an equilateral triangle, and the surrounding areas were inspected for cracks.

[0095] Table 1:

[0096]

[0097] As can be seen from Table 1, compared with the comparative examples, the graphene oxide grafted carbon fiber and the low-temperature water-based emulsion in the application together improve the anti-drilling crack performance of the cement-based thin plate panel material, which is more conducive to the installation of the thermal insulation board using metal fixing parts, improves the installation firmness and the safety of the external wall insulation board. In addition, the corrosion inhibitor can greatly improve the sulfate resistance grade of the panel material. In addition, controlling the water-cement ratio and the mortar ratio of the panel slurry can also make the panel material have better mechanical strength and corrosion resistance. The cement-based thin plate panel material prepared by the application has the advantages of not easy to crack, high mechanical lightness, can withstand external force impact in the process of transportation, stacking, drilling, glueing, fixing and installation, and also needs corrosion resistance, can resist acid gas or acid rain erosion. The panel is thin, has small self-weight and high safety in use. In the comparative example 4, although the amount of graphene oxide grafted carbon fiber, low-temperature water-based emulsion and cement is the same as that in example 1, the proportion of active materials such as secondary fly ash and silica fume is reduced, and the amount of water is increased, so the strength of the panel material decreases compared with example 1; in addition, the decrease of the corrosion inhibitor also leads to the decrease of the sulfate resistance grade.

[0098] Finally, it should be pointed out that: the above examples are only used to illustrate the technical solutions of the application, and not to limit them; although the application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing examples, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the application.

Claims

1. A panel material for a thermal insulation board, formed by curing a panel slurry, characterized in that: The formula of the panel slurry is as follows, calculated by mass percentage: 26-34% cement, 38-50% quartz sand, 3-10% secondary fly ash, 2-4% silica fume, 0.6-3% water reducer, 0.1-1% defoamer, 0.1-2% alkaline activator, 0.1-0.8% graphene oxide grafted carbon fiber, 0.05-1.5% carboxymethyl cellulose, 0.05-1% sodium gluconate, 0.8-2.5% anti-corrosion inhibitor, 0.5-2% low-temperature aqueous emulsion, and 10-16% water; the sum of the percentages of the aforementioned components is 100%.

2. The panel material according to claim 1, characterized in that The water-cement ratio of the panel slurry is 0.4-0.45, preferably 0.

43.

3. The panel material according to claim 1, characterized in that The mortar-sand ratio of the panel slurry is 0.87-0.92, preferably 0.

9.

4. The panel material according to claim 1, characterized in that The cement is a mixture of one or more of grades 42.5, 42.5R, 52.5, 52.5R, 62.5, and 62.5R, and is low-heat cement or medium-heat cement.

5. The panel material according to claim 1, characterized in that The quartz sand has a particle size of less than 5 mm; and the quartz sand with particle sizes of 0.1-1 mm, 1-3 mm, and 3-5 mm is combined in a mass ratio of 2-4:5:1-3.

6. The panel material according to claim 1, characterized in that The silica fume particle size is 0.1-0.2 μm, and the silicon content is greater than 90%.

7. The panel material according to claim 1, characterized in that The water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of 25-30%; the defoamer is a polyether defoamer with a solid content of 40-50%; the alkaline activator is a mixture of a 10-15% sodium hydroxide solution and water glass in a mass ratio of 1:2, stirred and evenly mixed; and the low-temperature aqueous emulsion is an aqueous polyurethane emulsion or an aqueous polyacrylic acid emulsion or a combination thereof.

8. The panel material according to claim 1, characterized in that The anti-corrosion inhibitor is preferably SBT-RMA (II) concrete high-efficiency preservative produced by Jiangsu Subote New Materials Co., Ltd.; the diameter of the graphene oxide grafted carbon fiber is 5-20 μm and the length is 6-10 mm.

9. The panel material according to claim 1, characterized in that The formula of the panel slurry is: 30% cement, 43% quartz sand, 6.9% secondary fly ash, 2.25% silica fume, 1% water reducer, 0.2% defoamer, 0.5% alkaline activator, 0.4% graphene oxide grafted carbon fiber, 0.1% carboxymethyl cellulose, 0.05% sodium gluconate, 1.5% anti-corrosion inhibitor, 1.5% low-temperature aqueous emulsion, and 12.6% water.

10. The method for preparing the panel material of the thermal insulation board according to any one of claims 1 to 9, characterized in that: It includes: S1. Stirring and mixing a water reducer, graphene oxide grafted carbon fiber, a low-temperature aqueous emulsion, and 30-35% water to obtain a mixture A; S2. Dry-mixing cement, quartz sand, secondary fly ash, and silica fume to obtain a mixture B; S3. Mixing mixture A, mixture B, defoaming agent, alkaline activator, carboxymethyl cellulose, sodium gluconate, corrosion inhibitor, and remaining water, and stirring to obtain panel slurry; S4. Pour the panel slurry into the mold, flatten it with high-frequency vibration in a vacuum state, press it into shape at a pressure of 1.5-3MPa, and cure it in a constant temperature water or steam environment of 35-45℃ for 24-48h before demoulding, grinding and polishing to obtain the panel material of the thermal insulation board.

Citation Information

Cited By

  • Sintering-free rigid heat insulation plate and preparation method thereof

    CN122187467A